PENGARUH MODEL PJBL BERBANTUAN MEDIA QUIZIZZ TERHADAP HASIL BELAJAR BAHASA INDONESIA DI KELAS V SD - Wulandari, Rizka Mei; Zumrotun, Erna; Wiranti, Dwiana Asih (Jurnal Holistika, 2024)
The research was prompted by the limited diversity in the application of learning models and the inadequate use of instructional media, leading to unsatisfactory learning results for fifth-grade students at SDN Ngablak 01 Cluwak Pati. This study aimed to investigate the impact of the Problem-Based Learning (PJBL) paradigm, supported by Quizizz media, on the learning outcomes of Indonesian language in fifth-grade students at SDN Ngablak 01 Cluwak Pati. The research methodology utilized a quantitative approach, adopting an experimental procedure with a one-group pretest-posttest design. The population comprised 17 fifth-grade pupils at SDN Ngablak 01 Cluwak Pati. The sampling strategy employed was saturation sampling due to the small population size of less than 30 students, namely 17 fifth-grade kids. Consequently, all fifth-grade classes were included as the sample for this study. Information was gathered utilizing a 10-item multiple-choice assessment tool. The data analysis conducted using SPSS indicated that the utilization of PJBL, supported by Quizizz media, had a noteworthy impact on the academic achievements of fifth-grade students at SDN Ngablak 01 Cluwak Pati in relation to comprehending the primary concept of paragraphs. This effect was demonstrated by the statistical significance of the t-test, with a p-value of 0.00 < 0.05, showing that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Moreover, during the regression test, the obtained significance value was 0.000, which is less than 0.05. This indicates that there is a significant influence between variable X and variable Y.